Non-American triatomine occurrence data (Reduviidae: Triatominae) - Ceccarelli, Soledad (2025)
The dataset is a compilation of Non-American triatomine (Hemiptera: Reduviidae: Triatominae) occurrences to complement the American triatomine information, representing together the most complete and integrated database available to date at a global scale. It was done by researchers from the Triatomine Laboratory (CEPAVE, CONICET-UNLP) and from the National Institute of Parasitic Diseases, Chinese Center for Tropical Diseases Research. The data corresponds to 16 species of the genera Linschosteus and Triatoma from Africa, Asia and Oceania between the years 1926 and 2022, including verified records with associated geographic coordinates, collection dates, and ecological information. Data were gathered through a systematic review of published literature and colleague-provided data, validated through expert consultation